The Future of Asthma Treatment - Louis-Philippe Boulet (Canadian Respiratory Journal)
In the past few years, significant progress has been made in the treatment of asthma with the development of bronchodilators with longer durations of action, more concentrated inhaled steroid formulations and new modes of administering antiasthma medication. Furthermore, the hey role of education in the management of asthma has been emphasized and many educational programs have been established. The recognition of the role of airway inflammation and structural changes in the physiopathology of asthma has led to a re-evaluation of asthma treatment guidelines. Anti-inflammatory drugs are now considered the mainstay of asthma therapy. An unprecedented number of new, potentially helpful agents have been developed and will soon be available. Among other expected developments are the identification and possible correction of genetic abnormalities responsible for the tendency to develop asthma and atopy, and prevention or functional and structural airway changes. This last goal will be achieved by improved environmental control, earlier use of more powerful and safe anti-inflammatory agents, as well as an increased involvement on the part of the asthma patient in treatment.